SARAWAK STATE ELECTION 2011: SURVEY OF MALAY VOTERS’ BEHAVIOUR IN BN CRITICAL AREAS OF N24 BETING MARO AND N30 SARIBAS - Mohd. Desa, Zalina; Sehat Omar, Arenawati (Journal of Techno-Social, 2013)
The 2011 Sarawak State Election (SSE 2011) has proved to be one of the most exciting and intense elections the country has seen throughout its almost 50 year history. Results from the state and general election have been alarming with the opposition parties increasing their seats in both the state and national level. Although Barisan Nasional (BN) managed to retain its two-thirds majority seats (55 out of 71) during SSE2011, it was still considered a major loss. The opposition managed to increase their seats in thestate legislative assembly from two in 2001 and then nine in 2006 to 16 in 2011. This clearly indicates a change in voting behaviour among the voters in Sarawak. In GE 2008, five state governments fell to the hands of various parliamentary opposition parties. Thus, it gives some impacts to both the ruling government and the opposition political parties. The declining of seats and majority votes obtained in certain areas indicated a preliminary warning to BN. In view of that, this research will seek to examine the Sarawak Malay voters’ behaviour in BN critical areas of N24 Beting Maro and N30 Saribas, Sarawak. Before state election in 2001, these two areas were under one constituency and considered as one of the few BN’s stronghold. Several factors have been accredited to the reasons behind BN’s significant drop in electoral seats. This paper focuses in determining the factors that contribute to the Malay voters’ decision; the candidate’s personality, ethnicity/race, and their experience. Furthermore, this paper looks into the level of acceptance of voters towards the political parties that originated from outside Sarawak. The findings reveal and signify a clear message to the BN that Malay voters were serious about making a change. Therefore, the upcoming General Election among the Malay voters of BN Sarawak will be facing its most challenging election.